CHROMOSOME CHARACTERIZATION OF THREE VARIETIES OF GINGER (Zingiber officinaleRosc.) - Budi Setiadi Daryono; Siti Nur Azizah Fauziati Rahma; Purnomo .; Sudarsono . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Giant ginger (Zingiber officinale Rosc. var. officinale), red ginger (Zingiber officinale Rosc. var. rubra) and small ginger (Zingiber officinale Rosc. var. amarum) are three varieties of Zingiber officinale Rosc. They have a lot of benefit and often used by Indonesian as a traditional drug. Moreover, they have a big chance to be use as a flavor in world wide. Therefore, research for their quality, quantity and continuity of supplyare needed. Characterization of their chromosomes is one effort for improving ginger cultivation. The objective of this research was to study mitotic time and chromosome characters of three varieties of ginger. Squashing method was used for chromosome preparation. The results showed that mitotic time of giant ginger is 09.00-10.05 am, red ginger is 09.00-10.30 am, while small ginger is 08.45-11.00 am. Chromosome number of giant ginger and small ginger are 2n=2x=30, while red ginger is 2n=2x=22. Giant ginger has R= 3,109, Red ginger has R = 3,206 and small ginger has R = 4,065. Based on chromosome characters it is revealed that relationship between giant ginger and red ginger is closer that of compare to small ginger. This result is important as basic information for improving the gingers production through breeding program.Key words: Zingiber officinale Rosc., mitotic time, chromosome characterization, squashmethod